Characterization and modeling of fluid–rock interaction effects resulting from the application of the CO2-WAG method in carbonate reservoirs : impacts on injectivity behavior and production during cycles - Marçon, Diogo Reato (2025)
Water alternating CO2 (CO2-WAG) injection is a well-established method for enhanced oil recovery and a promising option for geological carbon storage. The alternating injection of this gas with water also increases carbonate rock reactivity, which is higher than that in siliciclastic reservoirs, affecting the porosity and permeability near the well, thereby impacting the injectivity and well integrity. The composition of the produced water is also affected, increasing the potential for inorganic scaling. Moreover, reactivity also changes the pH of the produced water, thereby affecting material selection for producer wells. The characterization and modeling of such fluid–rock interaction effects are challenging but valuable for designing and optimizing the CO2-WAG process. In this thesis, the individual impacts of intrinsic reservoir parameters on the injectivity behavior and composition of produced water are investigated through reactive transport simulation. The main objectives are to establish the scenarios most susceptible to a downward trend and to a high scaling potential and then develop CO2- WAG operational strategies to minimize negative effects on oil production and CO2 storage capacity. The study revealed that inherent reservoir conditions that lead to a downward trend in water injectivity include, ranked by importance, reduced miscibility between injected CO2-rich gas and reservoir oil, water-wetness wettability, high vertical heterogeneity, and decreased calcite content in the reservoir mineralogy. Optimization led to a higher WAG ratio, shorter WAG cycle periods, increased injection rate, and greater CO2 content in the injected gas. Drawing from an extensive review of the literature, this study is the first comprehensive multi-scale examination incorporating the phenomenon of relative permeability hysteresis into reactive transport simulations when evaluating the effect of rock dissolution on injectivity behavior and production during CO2-WAG. This is crucial because these phenomena occur concurrently. Relative permeability hysteresis contributes to reducing injectivity, while rock dissolution tends to increase it. This study offers fresh insights for designing and optimization of the CO2-WAG methods in carbonate reservoirs.